Da'wah Training for Teenagers in the Ambulu Branch of Angkatan Muda Muhammadiyah (AMM) - Bashori, Dhofir Catur; Huwaida, Hasna (Mujtama Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to equip teenagers under the auspices of the Ambulu branch of Angkatan Muda Muhammadiyah (AMM) with the skills to preach in the midst of society. These teenagers have great potential to make changes through the messages they convey. Therefore, this potential must be able to be managed and maximized as well as possible. The approach used in this service activity is the Participatory Action Research (PAR) approach which involves community groups as objects of service in analyzing problems and planning activities. While the implementation method uses training and lecture methods in delivering service materials. Before the implementation of the service, several stages were carried out in the form of planning, implementation, and evaluation. Furthermore, they were asked to develop a follow-up agenda in the form of making preaching materials or lectures as a follow-up to this training activity. In the future, the Muhammadiyah Youth Force (AMM) is required to organize more positive activities in order to channel the potential of teenagers in the field of da'wah